Risk Assessment and Skin Test Outcomes in Contrast Media Hypersensitivity: A Single-Center Study - Sadi Aykan, Filiz; Çölkesen, Fatih; Kılınç, Mehmet; Evcen, Recep; Yıldız, Eray; Sağun, Ferhat; Arslan, Şevket (The European Research Journal, 2026)
Objectives: Contrast media can cause adverse reactions ranging from mild skin symptoms to anaphylaxis. Although the pathophysiology is not fully understood, various risk factors have been reported. This study aimed to evaluate the risk factors and skin tests in patients experiencing hypersensitivity reactions to contrast media. Methods: A total of 52 patients were included in the study. Patients experiencing contrast media-induced hypersensitivity reactions were evaluated for demographic and clinical characteristics, the type of contrast media used, and skin tests. They were compared with patients without a history of reactions. The patient group experiencing reactions was further divided into two groups: those with and without atopic disease. Results: The patient group experiencing reactions was older. Comorbidity was high, and cardiovascular disease was the most common. Reactions were most frequently immediate and grade 1 and 2 in severity. The skin was most commonly affected, and anaphylaxis was detected in 28.6%. Approximately one-third had comorbid atopic disease, and respiratory system diseases and Hashimoto’s thyroiditis were significantly more common in this group. In the group without comorbid atopic disease, malignancy and psychiatric disorders were more common, but not significantly so. Skin tests were negative in all groups. Conclusions: Hypersensitivity reactions related to contrast medium use are increasing. Unnecessary examinations and tests cause delays in patient follow-up and treatment. All physicians must recognize and appropriately manage patients and reactions at high risk for contrast medium-related hypersensitivity reactions. We believe our study will contribute to the literature in managing and raising awareness of these reactions.